The use of Introduction, Situation, Background, Assessment, and Recommendation handover in the COVID-19 pandemic and non-COVID clinical settings: a systematic review and meta-analysis - Lazzari, Carlo; Rabottini, Marco (Frontiers in Health Services, 2025)
IntroductionThe Introduction, Situation, Background, Assessment, and Recommendation (ISBAR) approach to clinical handovers assists healthcare providers in sharing information about patients within clinical teams and across health sectors while reducing information gaps and medical errors. However, despite its significance, uncertainties remain about the clear outcomes of applying ISBAR and training, especially in settings managing COVID-19 and those not dealing with the pandemic.MethodsThis review was conducted following the PRISMA guidelines. All the selected articles underwent a progressive check for bias and validity using GRADEpro GDT and RoB-2 as per Cochrane guidelines. This review utilized a meta-analysis of 29 studies and a critical narrative review of seminal articles to condense the non-numerical findings. All articles were checked for heterogeneity with the I2 coefficient. The extracted effect size was the common language effect size (CLES), with 95% confidence intervals.ResultsISBAR strengthens communication skills in clinical teams, increases self-confidence and efficacy among healthcare practitioners, improves interprofessional communication, reduces medical errors, and enhances patient safety.ConclusionsOur systematic review confirms that ISBAR handover improved the quality of care during the COVID-19 pandemic and non-COVID clinical practice. The limitation of this study is related to the lack of randomized controlled trials and blinding. Almost all studies were cross-sectional, which only provides information regarding associations but not causation.